2015
DOI: 10.1021/acs.nanolett.5b01697
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Tipless Pyramid Arrays for Cell Poration

Abstract: Improving the efficiency, cell survival, and throughput of methods to modify and control the genetic expression of cells is of great benefit to biology and medicine. We investigate, both computationally and experimentally, a nanostructured substrate made of tipless pyramids for plasmonic-induced transfection. By optimizing the geometrical parameters for an excitation wavelength of 800 nm, we demonstrate a 100-fold intensity enhancement of the electric near field at the cell-substrate contact area, while the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 20 publications
(49 reference statements)
0
26
0
Order By: Relevance
“…Plasmonic substrate-based methods operate with the same physical poration mechanism as plasmonic nanoparticles but use lithography techniques to precisely pattern a surface of nanostructures that are not ingested by the cell. Recent studies have also shown that plasmonic substrates can deliver a broad range of cargo, including fluorescent probes, plasmids, bacteria, and proteins into cells [8,18,19,33,34]. Despite providing promising intracellular delivery results, the cellular changes induced by plasmonic substrates at the single cell level are not well understood [8,18,34].…”
Section: Introductionmentioning
confidence: 99%
“…Plasmonic substrate-based methods operate with the same physical poration mechanism as plasmonic nanoparticles but use lithography techniques to precisely pattern a surface of nanostructures that are not ingested by the cell. Recent studies have also shown that plasmonic substrates can deliver a broad range of cargo, including fluorescent probes, plasmids, bacteria, and proteins into cells [8,18,19,33,34]. Despite providing promising intracellular delivery results, the cellular changes induced by plasmonic substrates at the single cell level are not well understood [8,18,34].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still a need for a high-efficiency, high-throughput, low-toxicity, cost-effective intracellular delivery technique that is applicable to a range of cells types for a range of cargoes. Plasmonic nanostructured surfaces may be a promising alternative to the currently available intracellular delivery techniques and utilize the unique ability of plasmonic structures to absorb laser light energy and transfer the energy to a confined volume within the nearby surrounding medium [31,39,[49][50][51][52]. Upon illumination with a short laser pulse, the laser light energy is strongly absorbed by the plasmonic nanostructures, resulting in a rise in temperature [1,[57][58][59].…”
Section: Resultsmentioning
confidence: 99%
“…Laser-activated nanostructured substrates bypass this potential toxicity problem, as cells can be cultured on the substrates, porated, and removed from the substrates (which remain intact) after intracellular delivery without leaving metallic particles within the cells [31,39,[49][50][51][52]. In this thesis we explore the fabrication of various thermoplasmonic nanostructured substrates for intracellular delivery and use the fabricated substrates to deliver a wide range of membrane-impermeable cargoes (dyes, dextrans, proteins, etc.)…”
Section: Laser-mediated Cell Poration For Intracellular Deliverymentioning
confidence: 99%
“…Optoporation is another physical membrane poration mode that can assist nanoneedle cell penetration, by applying focused laser pulses at the interaction region of cells with plasmonic nanoparticles, [ 162,163 ] nanopatterns, [ 164–166 ] or nanotubes. [ 51,52 ] The operating principle is that the stimulus of a femtosecond‐pulsed laser will elicit surface plasmon polaritons on the nanoneedle surface, which can decay into high‐energy electrons, or “hot electrons” ( Figure a).…”
Section: Assisted Penetrationmentioning
confidence: 99%